Cobalt-catalyzed chelation-assisted C-C bond formation via C-H bond activation - Gao, Ke (2014)
During the past decades, transition metal-catalyzed chelation-assisted C–H bond functionalization has been developed as an efficient and regioselective synthetic strategy. While this chemistry has met with significant success with expensive second-row transition metals, catalysis with cheaper first-row transition metals could lead to the development of cost-effective alternative catalysts as well as the discovery of new reactions.